2018
DOI: 10.1055/s-0038-1675634
|View full text |Cite
|
Sign up to set email alerts
|

Deep Plane Facelift: An Evaluation of the High-SMAS versus Standard Incision Points

Abstract: In surgery of the aging face, operative adjustments of the superficial musculoaponeurotic system (SMAS) enhance facial contours. The senior author has observed that the standard deep plane face lift entry points on the SMAS do not provide as much tissue movement in a vertical direction as high-SMAS deep plane face lift entry points. In this study, tissue movement was measured comparing the conventional SMAS entry point with a high-SMAS entry point for deep plane face lifts. Institutional review board approval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…On the contrary, photographs of less beautiful exaggerated malar augmentation abound in lay magazines and social media. Sand et al 39 reported objective intraoperative measurement of tissue movement at 3 points along the jawline in comparing deep-plane facelift with 2 different SMAS entry point suspension. Though this type of objective measurement is valuable to assess different vector lifts, its significance in determining aesthetic clinical outcome is doubtful.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, photographs of less beautiful exaggerated malar augmentation abound in lay magazines and social media. Sand et al 39 reported objective intraoperative measurement of tissue movement at 3 points along the jawline in comparing deep-plane facelift with 2 different SMAS entry point suspension. Though this type of objective measurement is valuable to assess different vector lifts, its significance in determining aesthetic clinical outcome is doubtful.…”
Section: Resultsmentioning
confidence: 99%